Design of “Immersive” Teaching Situation Simulation System for Law Course Based on Artificial Intelligence - Tian, Yanyan (Scientific programming, 2022)
The method of scene mapping provides a very effective technical support for classroom participants to roam freely in a virtual scene larger than the real space. When the virtual scene is larger than the area in the real space, the existing scene mapping method will cause distortion of the original virtual scene and affect the user’s roaming experience and visual experience. In order to obtain the scene map with low isometric distortion when the virtual scene scale is much larger than the real space, this paper proposes the block map to divide and group the roads in the virtual scene. For each group of roadblocks, the mapping is obtained by minimizing the isometric distortion energy of the mapping on the premise that the adjacent road blocks are smooth and continuous at the junction. The segmented roadblocks are mapped to the interior of the real intersections, and then the mapping of the whole scene is optimized globally to further reduce the isometric distortion of the whole mapping. Based on the above theories, the design scheme of immersive virtual legal reality classroom is proposed, including the overall framework of immersive virtual legal reality classroom, interactive scheme design, interactive behavior design, and required technical scheme, etc. The application technology, educational application, and application experience are analyzed in combination with the constructed immersive virtual legal reality scene for corresponding innovation and improvement. By applying immersive virtual reality technology in the field of education, the results show that the simulation system has good practicability and stronger stability and can provide a better immersive experience for law class participants.